Answer

Verified

412.2k+ views

**Hint:**We are given an equation of fourth degree and its roots are complex. We will first write the roots of the equation i. e., $\left( {x - a - ib} \right),\left( {x - a + ib} \right),\left( {x - b - ia} \right),\left( {x - b + ia} \right)$. Then, we will form an equation using the given roots and on simplification, we will compare it with the given equation. And, by comparison, we will find the values of a and b. After that we will check the availability of every option.

**Complete step-by-step answer:**We know that if an equation has real coefficients and imaginary roots, the roots always occur in pairs and the same situation is given in the question.

Now, let f (x) = 0 be the equation formed by the given roots $a \pm ib$ and $b \pm ia$.

Since, $a \pm ib$ and $b \pm ia$ are the roots of the f (x) = 0, then

$\left( {x - a - ib} \right),\left( {x - a + ib} \right),\left( {x - b - ia} \right),\left( {x - b + ia} \right)$ are the factors of the polynomial f (x).

Hence, the desired equation will be:

f (x) = $\left[ {\left( {x - a - ib} \right)\left( {x - a + ib} \right)\left( {x - b - ia} \right)\left( {x - b + ia} \right)} \right] = 0$

Now, when we have the equation, we will simplify this equation in terms of powers of x to make it easy for comparing the given equation with this.

Using the algebraic identity: $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$in the above equation, we get

$ \Rightarrow $f (x) = $\left[ {{{\left( {x - a} \right)}^2} - {{\left( {ib} \right)}^2}} \right]\left[ {{{\left( {x - b} \right)}^2} - {{\left( {ia} \right)}^2}} \right] = 0$

As we know that ${i^2} = - 1$, putting the value in the above equation, we get

$ \Rightarrow f(x) = \left[ {{{\left( {x - a} \right)}^2} + {b^2}} \right]\left[ {{{\left( {x - b} \right)}^2} + {a^2}} \right] = 0$

Opening the brackets using the identity: ${\left( {a - b} \right)^2} = {a^2} - 2ab + {b^2}$, we get

$ \Rightarrow f(x) = \left[ {{x^2} - 2ax + {a^2} + {b^2}} \right]\left[ {{x^2} - 2bx + {b^2} + {a^2}} \right] = 0$

On further simplification, we get

$f(x) = \left[ {{x^4} - 2a{x^3} + \left( {{a^2} + {b^2}} \right){x^2} + \left( {{a^2} + {b^2}} \right){x^2} - 2ax\left( {{a^2} + {b^2}} \right) + {{\left( {{a^2} + {b^2}} \right)}^2} - 2b{x^3} + 4ab{x^2} - 2bx\left( {{a^2} + {b^2}} \right)} \right] = 0$

Combining the terms with the same powers of x and then simplifying the terms, we get

$ \Rightarrow f(x) = \left[ {{x^4} - 2{x^3}\left( {a + b} \right) + 2{x^2}{{\left( {a + b} \right)}^2} - 2\left( {{a^2} + {b^2}} \right)\left( {a + b} \right)x + {{\left( {{a^2} + {b^2}} \right)}^2}} \right] = 0$

Now, we get an equation which is in only form of coefficient of different powers of x. hence, comparing this equation $ \Rightarrow f(x) = \left[ {{x^4} - 2{x^3}\left( {a + b} \right) + 2{x^2}{{\left( {a + b} \right)}^2} - 2\left( {{a^2} + {b^2}} \right)\left( {a + b} \right)x + {{\left( {{a^2} + {b^2}} \right)}^2}} \right] = 0$ with the given equation ${x^4} - 10{x^3} + 50{x^2} - 130x + 169 = 0$, we get

$

2(a + b) = 10 \\

2{(a + b)^2} = 50 \\

2({a^2} + {b^2})(a + b) = 130 \\

{({a^2} + {b^2})^2} = 169 \\

$

Checking for every option:

Option(A): (3, 2). If it is the value of (a, b) then it must satisfy the above mentioned condition.

$\therefore $ for 2(a + b) = 10 $ \Rightarrow 2\left( {3 + 2} \right) = 2\left( 5 \right) = 10$

Therefore, option (A) is correct.

Option(B): (2, 1). Again, it should satisfy the conditions.

For $2\left( {a + b} \right) = 10 \Rightarrow 2(2 + 1) = 2(3) = 6 \ne 10$

Hence, option(B) is incorrect.

Option(C): (-3, 2).

For $2(a + b) = 10 \Rightarrow 2( - 3 + 2) = 2( - 1) = - 2 \ne 10$

Hence, option(C) is incorrect.

Option(D): (-3, -2).

For $2(a + b) = 10 \Rightarrow 2( - 3 - 2) = 2( - 5) = - 10 \ne 10$

Therefore, option(D) is incorrect.

**Hence, option A is correct.**

**Note:**In such problems, it’s lengthy while solving the equations to reduce it into a simpler form. Such questions where roots are given and variables are required to find, you can also solve them by using the formula to form an equation of 4th degree. In this case you can directly solve by applying the formula 2(a+b) for the sum of the roots of a 4th degree equation.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Name 10 Living and Non living things class 9 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE